KEBIJAKAN ALOKASI DANA DESA DALAM MEMBANTU MEWUJUDKAN KEMANDIRIAN DESA: Studi Kasus di Desa Nyogan Kecamatan Mestong Kabupaten Muaro Jambi - Sinaga, Inriyani (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2017)
This article analyze about how the role of Local Self Government Fund Allocation (ADD) policy in helping achieving independence local self government. The research results show that the of ADD policy in local self government Nyogan Sub – district Mestong District Muaro Jambi is running well. This can be seen from the use of local self government fund allocation who has been through the plan drafting stage activities, activities implementation and accountability activities and have in accordance with regulation Regent in every year the budget that is 2014 up to 2016. As for some factors that influence of ADD policy in local self government Nyogan Sub – district Mestong District Muaro Jambi are communication, sources, behavior, bureaucracy structure, inveronment and size base and aim of policy. Advice writer of local self government fund allocation policy in helping to realize local self government independence is need arranging socialization local self government fund allocation to community and the implementation team so can know local self government fund allocation and its use so that public participation in any activity local self government fund allocation increases. The method of this research was qualitative with empiric researched approach. It was conducted in local self government Head’s Office Sub – district Mestong District Muaro Jambi. The data obtained by observing, interviewing, and literature review. The primary data obtained from informant and observation while the secondary data obtained from document and file of government rules in local self government Head’s Office at Nyogan, Sub – district Mestong District Muaro Jambi.